NECROPHILIA IN PERSPECTIVES OF INDONESIAN POSITIVE LAW AND ISLAMIC LAW - Febrian Arif Wicaksana; Arif Dian Santoso; Virgin Muthia Imron (Journal of Indonesian Comparative of Syari'ah Law, 2023)
the sexual crimes committed against corpses. In Indonesia, no law regulates the prohibition of Necrophilia. Meanwhile, Islam has specific and detailed laws governing Necrophilia, and most Indonesian people are Muslim so that it can be used as an illustration in the formation of positive law in Indonesia. Strengthen the judge's view of necrophilia perpetrators by implementing rechtvinding through various methods. From this background, in this study, there are two problem formulations. First, how is the necrophilia law in positive Indonesian law? Second, how is the law of Necrophilia in Indonesia from the perspective of Islamic law? This research aims to enforce the law, to reduce necrophilia crimes, and to create the deterrent effect. The research method used is normative juridical. The author uses literature research, statutory approaches, and comparisons between Islamic and positive Indonesian law. Followed by the documentation of study data collection techniques and qualitative data analysis techniques, followed by a deductive mindset. So that a theoretical basis can be formed, that, Necrophilia is reviewed in positive Indonesian law and Islamic law, and analysis of Necrophilia in positive Indonesian law and Islamic law. This study concluded that regarding positive Indonesian law, there are no rules that specifically regulate Necrophilia, as for some regulations that can be imposed in the form of criminal law in accordance with previous crimes such as murder, immorality, and others that can be imposed by judges. As for according to Islamic law, it can be imposed ta'zir or had.